High-peak-power flashlamp-pumped passively Q-switched Nd : YAG laser with AlGaInAs quantum wells as a saturable absorbers - art. no. 68712M - Liang, H. C.; Huang, J. Y.; Huang, S. C.; Su, K. W.; Chen, Y. F.; Huang, K. F. (My University, 2008)
We demonstrate an AlGaInAs saturable absorber with a periodic quantum wells (QWs)/barrier structure that can be used to achieve an efficient high-peak-power and high-pulse-energy passively flashlamp-pumped Q-switched Nd:YAG laser at 1.06 um. The barrier layers are designed to locate the QW groups in the region of the nodes of the lasing standing wave to avoid damage. With an incident pump voltage of 14.5 J, a single pulse was generated with a pulse energy of 14 mJ and a Q-switched pulse width of 13 ns. The maximum peak power was greater than 1.08 MW.
Keywords: flashlamp-pumped laser; semiconductor saturable absorber; passively Q-switched